Integrating bioinformatics with experimental validation unveils immunological and prognostic significance of PVRIG in pan-cancer - Peng Ma; Ruichen Zhang; Weili Sun (Scientific Reports)
Abstract The poliovirus receptor-related immunoglobulin domain-containing protein (PVRIG) is a recently identified immune checkpoint receptor predominantly expressed on natural killer and CD8 + T cells. This study investigated the role of PVRIG in the tumor immune microenvironment and its prognostic significance across various cancers. Using bioinformatics analyses, the study revealed that PVRIG expression is associated with immune cell infiltration, immune modulator gene expression, clinical outcomes, CD8 + T cell functionality, and responses to immunotherapies and targeted treatments. Additionally, in vitro and in vivo experiments confirmed that PVRIG plays a critical role in regulating CD8 + T cell functionality. These findings suggest that PVRIG could serve as a biomarker for prognosis and immune infiltration, as well as a promising target for novel cancer immunotherapies.